Characteristics of Leptospirosis Cases in Pacitan District, East Java Province - Prasetio, Firman Aji; Isfandiari, Muhammad Atoillah; Nugroho, Agung (Institute of Topical Disease Universitas Airlangga, 2022)
Leptospirosis is a disease that is still a public health problem in the world, however, these cases are rarely reported due to the difficulty of distinguishing clinical symptoms from other endemic diseases and the lack of appropriate laboratory diagnostic services. Pacitan district is one of the districts in East Java that reported Leptospirosis cases for 3 consecutive years from 2017 to 2019. There were total 92 Leptospirosis cases with Case Fatality Rate (CFR) of 15.22% in Pacitan. This study is a descriptive study with a Cross Sectional design that aims to describe the distribution of characteristics of Leptospirosis cases in Pacitan district based on person, place, and time. This study used secondary data from the Pacitan district Health Office, East Java province. The population in this study was all cases with Leptospirosis cases as many as 92 cases recorded in the Pacitan district Health Office data for 2017–2019. The sample of this study were all cases with Leptospirosis as many as 92 cases.The results of the study obtained Leptospirosis cases in Pacitan district in 2017–2019 based on person occured most in the age group of 40–49 years old by 20.45%, in the male sex by 68.48%, and in the population who worked as farmers by 73.58%. Based on the place where the most occured in Tulakan sub district by 52.75%, while based on time, most occured in February, March and April, this is because February to April is the rainy season. Therefore, based on the results of the study, it is necessary to educate the public, especially at risk groups, about the risk factors and Prevention of Leptospirosis.